Factors affecting the crop raiding behavior of wild rhesus macaques in Nepal: Implications for wildlife management. (1st November 2021) - Koirala, Sabina; Garber, Paul A.; Somasundaram, Deepakrishna; Katuwal, Hem Bahadur; Ren, Baoping; Huang, Chengming; Li, Ming
Abstract: In many areas of South Asia and Southeast Asia, macaques inhabiting agricultural landscapes are considered serious crop pests by local farmers. In Nepal, for example, the expansion of monocultures, increased forest fragmentation, the degradation of natural habitats, and changing agricultural practices have led to a significant increase in the frequency of human-macaque conflict. In order to more fully understand the set of factors that contribute to macaque crop raiding, and the set of preventive measures that can be put in place to avoid human-macaque conflict, we examined patterns of crop raiding by a group of 52 rhesus macaques ( Macaca mulatta ) in the Kavrepalanchok district, Nepal. We present data on macaque inflicted crop damage in 172 agricultural plots (each plot measuring 380 m 2 ) from August to October 2019. Our results indicate that farmland invasions by macaques were principally affected by crop type (maize was preferred over rice), nearness of farmland to both the forest edge and the major travel route used by the macaques, and the mitigation efforts applied by farmers to discourage crop raiding. We found that as the proportion of maize farmland in the most direct path from the macaque's main travel route to nearby crop raiding sites increased, the amount of maize damage decreased. This is likely explained by the fact that macaques traveling across several adjacent maize fields encounter multiple farmers protecting their crops. We estimated that the financial cost to individual farmer households of macaque maize and rice raiding was on average US 14.9 or 4.2% of their annual income from cultivating those two crops. As human-macaque conflict is one of the most critical challenges faced by wildlife managers in South Asia and Southeast Asia, studies of macaque crop raiding behavior provide an important starting point for developing effective strategies to manage human-macaque conflict while promoting both primate conservation and the economic well-being of the local community. Graphical abstract: Image 1 Highlights: In rural Nepal, crop raiding by macaques reduced farmer income by 4.2%. Crop type and distance from farm fields to the forest edge affected crop raiding. Planting buffer crops and collective monitoring are recommended to reduce crop loss. A program of natural forest restoration is needed in rural areas of Nepal.